2018
DOI: 10.1590/1414-431x20187046
|View full text |Cite|
|
Sign up to set email alerts
|

lncRNA CCAT1 promotes cell proliferation, migration, and invasion by down-regulation of miR-143 in FTC-133 thyroid carcinoma cell line

Abstract: Thyroid cancer is a common malignant tumor. Long non-coding RNA colon cancer-associated transcript 1 (lncRNA CCAT1) is highly expressed in many cancers; however, the molecular mechanism of CCAT1 in thyroid cancer remains unclear. Hence, this study aimed to investigate the effect of CCAT1 on human thyroid cancer cell line FTC-133. FTC-133 cells were transfected with CCAT1 expressing vector, CCAT1 shRNA, miR-143 mimic, and miR-143 inhibitor, respectively. After different treatments, cell viability, proliferation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…5,27 The signaling pathway activation plays a critical role in podocyte cytoskeleton structure stabilization and podocyte apoptosis inhibition. 17,25 Therefore, inhibition of CCAT1 in this study might regulate the activation of PI3K/Akt activation by either one of them, but this needs further investigation. It has been shown that the PI3K/Akt pathway can be regulated by the targets of CCAT1, including miR-143 and EGFR.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…5,27 The signaling pathway activation plays a critical role in podocyte cytoskeleton structure stabilization and podocyte apoptosis inhibition. 17,25 Therefore, inhibition of CCAT1 in this study might regulate the activation of PI3K/Akt activation by either one of them, but this needs further investigation. It has been shown that the PI3K/Akt pathway can be regulated by the targets of CCAT1, including miR-143 and EGFR.…”
Section: Discussionmentioning
confidence: 90%
“…17 By enhancing the stability of targeting protein, CCAT1 upregulates the expression level of the protein, such as Livin, a protein generally regarded as an apoptosis inhibitor in various malignancie. 12,25,26 All these indicate that CAAT1 is a master regulator, and can resultantly affect a variety of cellular signaling pathways, including Wnt/β-catenin, MEK/ERK1/2, and PI3K/AKT signaling pathways. 12,25,26 All these indicate that CAAT1 is a master regulator, and can resultantly affect a variety of cellular signaling pathways, including Wnt/β-catenin, MEK/ERK1/2, and PI3K/AKT signaling pathways.…”
Section: Discussionmentioning
confidence: 99%
“…K, CCAT1 exhibited different regulatory mechanisms in cellular nuclei and cytoplasm to promote malignant progression of prostate cancer. activate the PI3K/AKT and MAPK signaling pathways (27), as well as in non-small cell lung cancer, CCAT1 stimulates the elements of the Wnt signaling pathway by blocking Let-7c function (28). Similarly, the CCAT1/MIR-181a-5P/HOXA1 axis was shown to exert an oncogenic role in multiple myeloma (29).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lncRNA ZEB1‐AS1 is related with poor prognosis in NSCLC and promotes cancer cell metastasis (Liu et al, ). Furthermore, CCAT1 promotes cell growth, migration, and invasion of thyroid carcinoma cell via down‐regulation of miR‐143 (Yang et al, ). In ER‐positive breast cancer, MIAT is estrogen‐responsive and promotes estrogen‐induced growth of cancer cell (Luan et al, ).…”
Section: Introductionmentioning
confidence: 99%